Studi Penelusuran Kesesuaian Kurikulum Program Studi Sarjana Seni Musik Terhadap Kebutuhan Dunia Kerja - Ayub Prasetiyo (PROMUSIKA, 2015)
In the past thirty one years, the Music Department of ISI Yogyakarta has contributed to the development of music in Indonesia as the agent of change to build the human resources in the field of Western music. However, there has been no attempt to establish a relationship to the alumni of Music Departmentto provide contributions for the development Music Department of ISI Yogyakarta. Therefore, this research aims to search the Alumni of Music Department of ISI Yogyakarta in the period time of 2002 until 2012 in order to get the profile of the alumni and also to get the feedback on the suitability of the curriculum in Music Department to the needs of the workforce. This research uses qualitative method with descriptive statistical approach. The data collected by simple random sampling with 61 respondents from the alumni of Music Department of ISI Yogyakarta which spread all over Indonesia. The result of this research revealed that the learning process in Music Department of ISI Yogyakarta is able to provide supplies competence to compete in workforce. According to the data most of alumni of Music Department of ISI Yogyakarta are music educators. As a suggestion to meet the work forcerequirement as music educators, there should be additional skill for students (soft skills) such as organizational skills,  leadership, oral communication and the experience in community empowerment.